John Bull in Perplexity or Ascendancy versus Union. - (:unkn) unknown (McLean, Thomas, 1829)
Scholarly notes may be added at a later date.
Westminster Review No 19
1 print : col.
Keywords: Caricatures; Cartoons; Great Britain -- Politics and government -- 1800-1837; John Bull (Symbolic character)